Letter : International Solidarity Fund - Stott, William
034-0120-001 RAILWAY CLERKS' ASSOCIATION OF GREAT BRITAIN AND IRELAND Telegraphic Address: FORESHADOW NORWEST LONDON (as two words) Telephone: TERMINUS 6267 (3 lines) General Secretary WILLIAM STOTT Representing the Clerical, Administrative, Professional, Technical and Supervisory Employer in all Departments of the Railways and Allied Undertakings, and London Transport. Reference P. Registered Office: 25 EUSTON ROAD LONDON N.W.1 9th June, 1938. Sir Walter Citrine, K.B.E., General Secretary, Trades Union Congress, Smith Square, Westminster, S.W.1. Dear Sir Walter, INTERNATIONAL SOLIDARITY FUND. In accordance with a resolution carried at our recent Annual Conference members of the Association are being specially invited to subscribe to the International Solidarity Fund, the amount collected to be sent to you and earmarked for Relief in Spain. In order to help the appeal I have ordered from your office 1,000 copies of the Summarised Report of Relief Work in Spain undertaken by the International Solidarity Fund, and as the appeal is being held up until I receive those copies I hope you will not keep me waiting very long. At our Conference there was a proposal from one of our Branches that £500 should be sent to the International Brigade Dependants and Wounded Aid Committee, and as I have received an appeal direct from the Secretary of that Committee I wish you would let me know whether any of the monies which have been sent to the T.U.C. has been allocated to the International Brigade, and whether you consider that the R.C.A. should contribute towards that Brigade. I have also received an appeal from the Secretary of the Relief Committee for Victims of Fascism, and perhaps you will tell me whether that Committee has received any financial support from or through the T.U.C. Yours sincerely W. Stott 292/946/34/120